Proposed two-dimensional topological insulator in SiTe - Ma, Yandong; Kou, Liangzhi; Dai, Ying; Heine, Thomas (Physical Review B, 2016)
The two-dimensional (2D) crystal SiTe is identified to be a 2D topological insulator (TI) with bulk band gap of 220 meV by means of first-principles calculations. The synthesis of 2D SiTe has been reported earlier [Phys. Status Solidi RRL 8, 302 (2014)10.1002/pssr.201409013] as part of a three-dimensional superlattice. The freestanding monolayer is thermally and dynamically stable and only weakly bound within the layered superlattice, offering the possibility of mechanical exfoliation. Our discovery of a topological signature with large band gap raises the expectation that the most apparent showstopper in experimental 2D TI research, the lack of stable materials exposing a quantum spin Hall effect at room temperature, can be overcome. This offers many laboratories an opportunity to participate in investigating exciting new phenomena in condensed matter physics, such as new quasiparticles and dissipationless spin transport.
CRIS-Team Scopus Importer:2023-03-20